Design Of Wood Pellet Factory For Co-Firing Production Of Coal-Fired Power Plant In Tanjung Enim - Muhammad Zaki; Endang Chumaidiyah; Yudha Prambudia (Jurnal Indonesia Sosial Teknologi, 2023)
Climate change is one of the leading causes that threaten life on Earth. Indonesia's efforts to overcome this problem are by signing the COP26 Coal to Clean Power Transition Statement or a statement on the transition from coal energy to clean energy. This commitment to clean energy is targeted to reach net zero emissions by 2060. The company wants to expand its business into the new and renewable energy (EBT) sector. Therefore, before the company develops its business to establish a wood pellet factory, it is necessary first to design the initial business and business feasibility, which includes aspects of feasibility analysis, including market aspects, technical aspects, environmental aspects, financial aspects, and sensitivity analysis to be able to determine whether this business development decision is feasible to run or not. The inflation rate is 3.27%, and the MARR value is 8%. Based on the feasibility calculation on the financial aspect, the establishment of a wood pellet factory is feasible with an NPV of Rp 29,393,458,729, IRR of 44.34%, PBP for 2.28 years, and BCR of 1.29. According to sensitivity analysis, the establishment of this wood pellet factory is sensitive to a decrease in product selling prices by 12.01%, sensitive to an increase in direct raw material costs by 41.57% and sensitive to an increase in raw material supply service costs by 51.46%.